Optimalisasi Produktivitas Lahan Sempit di Desa Sigerongan Lingsar Lombok Barat melalui Penerapan Tumpangsari Sayuran Okra dan Beberapa Genotipe Kacang Tanah - A. Farid Hemon; Sumarjan Sumarjan; Baiq Erna Listiana (Jurnal SIAR ILMUWAN TANI, 2020)
This extension activity aimed to help Farmer Group partner of the "Sumber Hidup" in Sigerongan Village to increased the productivity of narrow land through the application of intercropping technology between okra crop and peanut genotypes. The program that implemented were the application of science and technology with stages of activities, namely: 1) dissemination activities "optimization of productivity of narrow land through the application of intercropping okra and peanuts and the application of technology to increased production of okra and peanut”. This activity was carried out with a lecture and discussion system between the Extension Team and the Farmer Group, and 2) plot demonstration program. Farmers directly participated in planing, planting, crop maintaining, comparing and evaluating whether the implemented program will benefit or not. The results of the activity showed that the farmers participating in the extension were very responsive to the dissemination of intercropping okra-peanut. This was reflected in the participants' enthusiasm in asking questions and having discussions between participants with Team. In addition, participants were also active in participating in each stage of activities such as selecting seed quality, making demonstration plots, planting, growing, weeding, controlling pests and diseases, and harvesting activities. The transformation process of the okra-peanut intercropping technology in the narrow land of Sigerongan Village has implemented, with the hope that farmers will be able to take advantage the narrow land by planting intercropping. Cultivation of okra-peanut intercropping was more productive with an LER value of 2.28 compared to peanut monoculture and 1.35 compared to okra monoculture